Sikap Percaya Diri dalam Kegiatan Ekstrakurikuler Seni Tari - Lola Manera; Dwi Anggraini (JURIDIKDAS, 2023)
This study discusses to attitude of confidence in the dance movement of Bengkulu Province offerings in extracurricular activities of SD Negeri 01 Bengkulu City students. The method used is descriptive and the type of research used is qualitative naturalistuk. The subjects of the research were grade students extracurricular for dance. The research instrument was the researcher himself using student observation guidelines and interview guides for students and dance coaches. Data collection techniques using interviews and observations, while for data analysis using data reduction techniques, data presentation, and drawing conclusions from Miles and Huberman. Test the credibility of the data through increasing perseverance and member checking. The results of this study indicate that students perform wiraga movements, body movements involving elements of the body, wirama that is in harmony with music, and wirasa, ie movements with a smiling face in accordance with the provisions of the dance offerings of Bengkulu Province. Forms of students' self-confidence that appear during dance extracurricular activities are students who dare to do, students are enthusiastic in dancing, students are enthusiastic in dance extracurricular activities, students are independent in dance extracurricular activities, students are responsible for dance extracurricular activities and are able to get along. Confidence in extracurricular dance at SD Negeri 01 Bengkulu City has not yet been awakened. All children are influenced by the emotional aspects related to mood, affect the mind from anxiety so students can be calm by showing smiling face expressions, and movements of limbs in harmony with music.